A study of prevalence of culture positive UTI in children: clinical profile, risk factor analysis, and microbiological profile - Rajendran, K.; Shankar, Kiruba (International Journal of Contemporary Pediatrics, 2019)
Background: Urinary infection is one of the common infections occurring in children. Different literature says different definition for UTI. Indian Academy of Pediatrics defines urinary tract infection as the growth of a significant number of organisms of single species in urine culture with the presence of symptoms of UTI. The objective is to study the clinical profile of children with urine culture positive UTI. Methods: The study was conducted in Kovai medical centre and hospital Coimbatore. The sample size is 150 children. The study population includes children with culture-positive UTI who are admitted between October 2015 to September 2016 over a period of 1 year. Child’s history was then recorded as answers to the pre-prepared questionnaire in a proforma. Clinical examination was done, and the findings were recorded. Blood sampling was done for all patients and sent to a laboratory to measure total count, differential count, ESR. Results: Previous urinary tract infection was present in 2.7% of children. All children had the same organism grown in urine culture as in previous episode suggesting unresolved or persistent bacteremia. This is comparable with the literature stating unresolved bacteremia as the most common type of recurrent. Conclusions: The study group in which the risk factors were analysed had a female preponderance (may be due to the short urethra, easy ascending infection). In present study population fever and increased frequency are two important symptoms followed by abdominal pain.